Structural and Mechanical Properties of Orthorhombic Libeh3: AB-Initio Study - Rahrah M.; Lebga N.; Latreche A.; Daoud S.; Benmakhlouf A. (Annals of West University of Timisoara: Physics)
The structural parameters and the elastic properties of orthorhombic LiBeH3 material were predicted theoretically using the density functional theory (DFT). The exchange-correlation potential term was treated using the local density approximation (LDA). Our values of the structural parameters and elastic constants predicted for LiBeH3 material agree well with other results of the literature.